Estimating discharge dates using routinely collected data: improving the preparedness of parents of preterm infants for discharge home. Issue 2 (3rd October 2016) - Fleming, Peter J; Ingram, Jennifer; Johnson, Debbie; Blair, Peter S
Abstract : The length of stay for moderately preterm infants has progressively become shorter in the UK in recent years but staff still commonly inform parents that their baby will go home around their estimated date of delivery (EDD). Parents need as much notice as possible to prepare for the discharge of their baby, and to gain the necessary skills and knowledge to care for their infant safely. We report the use of routinely collected neonatal data to develop and implement a simple centile chart for date of discharge from hospital, which allows staff and parents to predict the likely discharge date more accurately for preterm infants, most of whom now go home more than 3 weeks before their EDD. This information allows better and timelier planning for discharge of such infants, by parents and staff.